Current perspectives of bio-ceramic technology in endodontics: calcium enriched mixture cement - review of its composition, properties and applications - Shivani Utneja; Ruchika Roongta Nawal; Sangeeta Talwar; Mahesh Verma (Korean Academy of Conservative Dentistry, 2015)
Advancements in bio-ceramic technology has revolutionised endodontic material science by enhancing the treatment outcome for patients. This class of dental materials conciliates excellent biocompatibility with high osseoconductivity that render them ideal for endodontic care. Few recently introduced bio-ceramic materials have shown considerable clinical success over their early generations in terms of good handling characteristics. Calcium enriched mixture (CEM) cement, Endosequence sealer, and root repair materials, Biodentine and BioAggregate are the new classes of bio-ceramic materials. The aim of this literature review is to present investigations regarding properties and applications of CEM cement in endodontics. A review of the existing literature was performed by using electronic and hand searching methods for CEM cement from January 2006 to December 2013. CEM cement has a different chemical composition from that of mineral trioxide aggregate (MTA) but has similar clinical applications. It combines the biocompatibility of MTA with more efficient characteristics, such as significantly shorter setting time, good handling characteristics, no staining of tooth and effective seal against bacterial leakage.